2010
DOI: 10.1152/ajpcell.00267.2009
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Ca2+ sparklet activity during acute hyperglycemia and diabetes in cerebral arterial smooth muscle cells

Abstract: Ca(+) sparklets are subcellular Ca(2+) signals produced by the opening of L-type Ca(2+) channels (LTCCs). In cerebral arterial myocytes, Ca(2+) sparklet activity varies regionally, resulting in low and high activity, "persistent" Ca(2+) sparklet sites. Although increased Ca(2+) influx via LTCCs in arterial myocytes has been implicated in the chain of events contributing to vascular dysfunction during acute hyperglycemia and diabetes, the mechanisms underlying these pathological changes remain unclear. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
134
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(155 citation statements)
references
References 58 publications
19
134
1
1
Order By: Relevance
“…Although this will decrease [Ca 2ϩ ] i and lead to smooth muscle relaxation, increasing the Ca 2ϩ load of the SR will also lead to faster turn around and increased release of Ca 2ϩ from the stores upon subsequent and/or continuous activation. Indeed, PKA increases Ca 2ϩ -spark frequency mediated by SR ryanodine receptor channels (RyR) (18,30,47). It is possible that PKA not only regulates SR Ca 2ϩ through SERCA and RyR channels but also by activating the store-operated channels responsible for replenishing the SR. PKA has recently been shown to activate the heteromeric Orai1/Orai3 channel through phosphorylation of STIM1 in HEK-293 cells (43).…”
Section: Discussionmentioning
confidence: 99%
“…Although this will decrease [Ca 2ϩ ] i and lead to smooth muscle relaxation, increasing the Ca 2ϩ load of the SR will also lead to faster turn around and increased release of Ca 2ϩ from the stores upon subsequent and/or continuous activation. Indeed, PKA increases Ca 2ϩ -spark frequency mediated by SR ryanodine receptor channels (RyR) (18,30,47). It is possible that PKA not only regulates SR Ca 2ϩ through SERCA and RyR channels but also by activating the store-operated channels responsible for replenishing the SR. PKA has recently been shown to activate the heteromeric Orai1/Orai3 channel through phosphorylation of STIM1 in HEK-293 cells (43).…”
Section: Discussionmentioning
confidence: 99%
“…For example, McGinty et al 35 found decreased VDCC activity in pericytes cultured in 25 mM glucose. However, perhaps because hyperglycemia in vitro does not fully mimic diabetes, our study of microvascular complexes did not reveal a significant effect of diabetes on VDCC function in the pericyte-containing capillaries.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports suggest that hyperglycemia and diabetes can promote persistent calcium sparklet activity via activation of L-type calcium channels in arterial smooth muscle (70,71). Interestingly, sparklet activity is controlled by PKC and underlies a sustained calcium entry through persistent L-type channel activity (72).…”
Section: No Diabetesmentioning
confidence: 99%